Family alcohol use, rather than childhood trauma, is more likely to cause male alcohol use disorder: findings from a case-control study in northern China - Xu Chen (BMC, 2021)
Abstract Objective To explore the influence of childhood trauma and family alcohol use on male alcohol use disorder. Methods We conducted a case-control study using Childhood Trauma Questionnaire (CTQ) and a structured interview involving 129 men with alcohol use disorder and 129 healthy male volunteers. The two groups were compared in terms of childhood trauma, parental drinking behavior, and attitudes toward childhood drinking. Results Patients showed higher scores of CTQ than controls on childhood trauma experiences, including on the subscales of physical abuse, emotional abuse, sexual abuse, and emotional neglect. Higher proportions of patients than controls had fathers who drank seven or more times a week, and had mothers who were opposed to childhood drinking. Conversely, a smaller proportion of patients than controls had fathers who opposed childhood drinking. Patients were more likely than controls to have been induced to drink as children. Logistic regression analysis identified three risk factors for alcohol use disorder: induced drinking during childhood [odds ratio (OR) 6.09, 95% confidence interval (CI) 2.56–14.51], the father’s weekly alcohol consumption during the respondent’s childhood (OR 4.40, 95%CI 2.94–6.58) and history of smoking (OR 3.39, 95%CI 1.48–7.77). Conversely, more years of education were a protective factor against alcohol use disorder (OR 0.88, 95% CI 0.78–0.99). Conclusions Men whose fathers drank frequently during their childhood and were encouraged to drink may be at increased risk of alcohol use disorder in adulthood. In fact these factors of family alcohol use appear to increase risk of alcohol use disorder among adult men more than exposure to childhood trauma does.